Making it Easier for Women in Malawi to Formalize Their Firms and Access Financial Services - Campos, Francisco; Goldstein, Markus; McKenzie, David (World Bank, Washington, DC, 2016)
The global rate of informal firms is high, especially for those that are women-owned and in the poorest countries, despite 149 economies implementing 368 reforms to simplify the registration process in a recent ten-year period. Through an experiment in Malawi, the author established an effective and replicable design to offer informal firms support to formalize, costing much less than the typical private sector development intervention. What works in the short-term is combining business registration with an information session at a bank including the offer of a business bank account. This led to women entrepreneurs increasing usage of bank accounts for business-only purposes, financial record keeping, and access to other financial services including insurance. Informal firms are smaller and less productive than formal ones, and their informal status is often associated with a number of costs, including less access to finance. Although 75 percent of the countries included in the Doing Business project have adopted at least one reform making it easier to register a business since 2004, informality remains very prevalent, especially in Sub-Saharan Africa. This may lead many to believe that entrepreneurs are not interested in registering their firms, and that if they could only be convinced to formalize it would lead to great benefits for their business.